Exponential inequalities for Mann's iterative scheme with functional random errors. Issue 1 (2nd January 2018) - Barache, Bahia; Arab, Idir; Dahmani, Abdelnasser
ABSTRACT: In this article, we deal with an iteration method for approximating a fixed point of a contraction mapping using Mann's algorithm under functional random errors. We first show its almost complete convergence to the fixed point by mean of an exponential inequality and then we specify the induced rate of convergence. We finally build a confidence domain for the fixed point. Moreover, some numerical examples are considered.